Synergistic Function via Amorphous and Nanoscale Polarization Heterogeneous Regions in (1−x)BaTiO3‐xBi(Ni0.5Zr0.5)O3 Thin Film with Ultrahigh Energy Storage Capability and Stability. Issue 11 (15th September 2021) - Huang, Rui; Wang, Hongye; Tao, Cheng; Cao, Minghe; Hao, Hua; Yao, Zhonghua; Liu, Hanxing
Abstract: Dielectric film capacitors are considered as potential candidates for advanced power electronics technology due to their extremely high‐power densities and outstanding mechanical and thermal stability, but the further improvement of energy storage density is still needed. Here, a strategy is proposed to enhance the energy storage properties by introducing nanoscale polarization regions into amorphous films, which can significantly improve the maximum polarization and maintain a high breakdown strength. The (1− x )BaTiO3 ‐ x Bi(Ni0.5 Zr0.5 )O3 ((1− x )BT‐ x BNZ) thin films are fabricated by the sol–gel method and the amorphous films with nanoscale polarization regions are obtained by adjusting the preparation process. Consistent with the conjecture, amorphous phase and nanoscale polarization regions in the (1− x )BT‐ x BNZ films are clearly observed by electron diffraction. Results show that giant recoverable energy density of 103.7 J cm −3 with high energy efficiency of 88.3% are simultaneously achieved at 8.3 MV cm −1 in 0.92BT‐0.08BNZ thin films. Furthermore, the 0.92BT‐0.08BNZ thin film exhibits excellent thermal stability in a wide temperature range of 20–200 °C, ∆ W rec / W rec20 °C  < 2.2%. This work provides a novel method for dielectric thin film capacitors applied in high temperature and electric field. Abstract : A novel amorphous thin film capacitor with nanoscale polarization regions provides an effective method to significantly enhance the breakdown strength. 0.92BaTiO3 ‐0.08Bi(Ni0.5 Zr0.5 )O3 thin film obtains an ultrahigh energy storage density of 103.7J cm −3 with an efficiency of 88.3% under a high breakdown strength of 8.3 MV cm −1 .